Ploughs of land reform in the Hinterlands of the São Francisco: the experiences of Peba and Lameirão, Delmiro Gouveia, Alagoas, 1986-1989 - Silva, Aline Oliveira; Vieira da Cruz, José (Revista Crítica Histórica, 2023)
Versão em inglês.